Point stresses during reproductive stage rather than warming seasonal temperature determine yield in temperate rice - Matthew B. Espe; Jim E. Hill; Robert J. Hijmans; Kent McKenzie; Randall Mutters; Luis A. Espino; Michelle Leinfelder‐Miles; Chris van Kessel; Bruce A. Linquist (Global Change Biology, 2017)
Climate change is predicted to shift temperature regimes in most agricultural areas with temperature changes expected to impact yields of most crops, including rice. These temperature‐driven effects can be classified into point stresses, where a temperature event during a sensitive stage drives a reduction in yield, or seasonal warming losses, where raised temperature is thought to increase maintenance energy demands and thereby decrease available resources for yield formation. Simultaneous estimation of the magnitude of each temperature effect on yield has not been well documented due to the inherent difficulty in separating their effects. We simultaneously quantified the magnitude of each effect for a temperate rice production system using a large data set covering multiple locations with data collected from 1995 to 2015, combined with a unique probability‐based modeling approach. Point stresses, primarily cold stress during the reproductive stages (booting and flowering), were found to have the largest impact on yield (over 3 Mg/ha estimated yield losses). Contrary to previous reports, yield losses caused by increased temperatures, both seasonal and during grain‐filling, were found to be small (approximately 1–2% loss per °C). Occurrences of cool temperature events during reproductive stages were found to be persistent over the study period, and within season, the likelihood of a cool temperature event increased when flowering occurred later in the season. Short and medium grain types, typically recommended for cool regions, were found to be more tolerant of cool temperatures but more sensitive to heat compared to long grain cultivars. These results suggest that for temperate rice systems, the occurrence of periodic stress events may currently overshadow the impacts of general warming temperature on crop production.

Water balances and evapotranspiration in water- and dry-seeded rice systems - Bruce Linquist; Richard Snyder; Frank Anderson; Luis Espino; Guglielmo Inglese; Serena Marras; Ruben Moratiel; Randall Mutters; Placido Nicolosi; Honza Rejmanek; Alfonso Russo; Tom Shapland; et al. (Irrigation Science, 2015)